2003
DOI: 10.1016/s0194-5998(03)01577-8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope affects decision making in cholesteatoma surgery

Abstract: Our results showed that the use of the endoscope gave the surgeon better control over the pathology, thus achieving better eradication. Stated differently, the use of the endoscope raised the surgeon's confidence level about total removal and thus encouraged the surgeon to keep the canal wall intact while removing cholesteatoma in hidden areas. Therefore, the use of endoscope could be considered an additional tool that may affect decision-making in cholesteatoma surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 13 publications
3
45
0
8
Order By: Relevance
“…(15,20) The cholesteatoma was lying deep in sinus tympani in these cases which could only be viewed by angled telescope and removal of stapes suprastructure was necessary to eradicate the disease from this area. Thus, we agree with Ajalloueyan M et.al 7 and El-Meselaty k et.al 21 that usage of otoendoscope in cholesteatoma surgery is important as it will help to reduce the incidence of residual disease in mastoid surgery. The principle of creating a dry and self-cleaning mastoid cavity involves extensive surgery.…”
Section: Discussionsupporting
confidence: 91%
“…(15,20) The cholesteatoma was lying deep in sinus tympani in these cases which could only be viewed by angled telescope and removal of stapes suprastructure was necessary to eradicate the disease from this area. Thus, we agree with Ajalloueyan M et.al 7 and El-Meselaty k et.al 21 that usage of otoendoscope in cholesteatoma surgery is important as it will help to reduce the incidence of residual disease in mastoid surgery. The principle of creating a dry and self-cleaning mastoid cavity involves extensive surgery.…”
Section: Discussionsupporting
confidence: 91%
“…In otologic practice, due to the complex anatomic structure of the surgical area, the use of endoscopes has risen during the past three decades. During the past 10 years, the incidence of radical ear surgery reduced due to the widespread use of the endoscopes in otologic surgical procedures [3,11]. Endoscopes are illuminated by fiber optic cables parallel to the optical system of the light source.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested the use of endoscopes with different angles to explore the sinus tympani; especially 30, 45 and 70°telescopes allow a better control of the middle ear cavity. Badr-El-Dine [6] and El-Meselaty et al [19] studied utility of the endoscope during cholesteatoma surgery and they found that endoscopic approach to sinus tympani gave a better exposition of the sinus thus achieving better pathology eradication.…”
Section: Retrotympanic Spacesmentioning
confidence: 99%
“…This is confirmed by other studies reported in international literature, which showed the same results. This is particularly true especially when the sinus tympani is deep [19][20][21][22]. For this reason it might be very useful for the surgeon to study the extension of the ST before the surgery.…”
Section: Retrotympanic Spacesmentioning
confidence: 99%